Characterization of Extractable Species from Polypropylene Microplates. (December 2018) - Hill, Eric J.; Martin, Steve J.; Weikart, Christopher M.
The use of microplates (for bioassays, immunoassays, and general research) that are manufactured from plastic materials has proved problematic due to issues with accuracy, repeatability, and specificity of the results generated. The cause of these issues has been identified as leachables present in the plastic materials. This article presents an extractables study performed with available microplates manufactured with plastic. Common microplates from five different vendors were obtained, including plates from SiO2 Medical Products (SIO) containing a plasma treatment designed to produce an ultra-low protein-binding surface. The microplates were solvent extracted, and the resulting extracts were analyzed for organic extractables. The extractables profiles were examined and compared among the five different plate types. Detected extractables were identified in each of the extracts, and the potential effect on protein binding is discussed.